REFORM OF PUBLIC INVESTMENT MANAGEMENT IN UKRAINE: RISKS AND CHALLENGES OF PRACTICAL IMPLEMENTATION - IVASHKO, Olena (Scientific journal «World of Finance», 2026)
Вступ. Реформа управління публічними інвестиціями в Україні є надзвичайно актуальною в сучасних економічних та соціальних умовах. Наслідки війни та значні руйнування інфраструктури вимагають ефективного використання державних інвестиційних ресурсів для відновлення економіки та підвищення її стійкості. Водночас обмеженість державного бюджету, залежність від міжнародної фінансової допомоги та складність координації численних інвестиційних проєктів створюють низку ризиків і викликів для практичної реалізації реформ.Дослідження цих проблем дає змогу виявити ефективні підходи до планування, фінансування та контролю публічних інвестицій, що має безпосередній вплив на економічний розвиток країни та добробут її населення. Саме тому реформування системи управління публічними інвестиціями є важливою як для наукового аналізу, так і для практичної реалізації державної політики.Мета – проаналізувати ризики і виклики практичної реалізації реформи управління публічними інвестиціями в Україні та обґрунтувати напрями підвищення ефективності функціонування відповідної системи в умовах трансформаційних змін.Результати. Проаналізовано ключові елементи реформи управління публічними інвестиціями, зокрема запровадження Єдиного проєктного портфеля публічних інвестицій та нових підходів до пріоритезації інвестиційних проєктів. Виявлено основні ризики практичної реалізації реформи, серед яких інституційна спроможність органів публічної влади, якість підготовки проєктної документації, кадрові та аналітичні обмеження, а також нерівномірність регіонального розвитку.Висновки. Обґрунтовано, що успішність реформи управління публічними інвестиціями залежить від узгодженості стратегічних і бюджетних рішень, підвищення управлінських компетенцій та посилення прозорості інвестиційних процесів. Запропоновано напрями мінімізації ризиків реалізації реформи в контексті післявоєнного відновлення України.Introduction. Reforming public investment management in Ukraine is extremely relevant in the current economic and social conditions. The consequences of the war and significant infrastructure destruction require the effective use of state investment resources to restore the economy and increase its resilience. At the same time, the limited state budget, dependence on international financial assistance, and the complexity of coordinating numerous investment projects create a number of risks and challenges for the practical implementation of reforms.Research into these issues allows us to identify effective approaches to planning, financing, and controlling public investment, which has a direct impact on the country's economic development and the well-being of its population. That is why reforming the public investment management system is important both for scientific analysis and for the practical implementation of public policy.The purpose of the article is to analyse the risks and challenges of the practical implementation of public investment management reform in Ukraine and to justify ways of improving the efficiency of the relevant system in the context of transformational changes.Results. The article analyses key elements of public investment management reform, including the introduction of a unified public investment project portfolio and new approaches to prioritising investment projects. The main risks of practical implementation of the reform have been identified, including the institutional capacity of public authorities, the quality of project documentation preparation, personnel and analytical constraints, and uneven regional development.Conclusions. It is argued that the success of public investment management reform depends on the consistency of strategic and budgetary decisions, the improvement of management competencies, and the enhancement of the transparency of investment processes. Directions for minimising the risks of reform implementation in the context of Ukraine's post-war recovery are proposed.